Synchronised Object Retrieval: the enhancement of information retrieval performance in multimedia environments using synchronisation protocols - Brophy P. (Information Research: An International Electronic Journal)
The retrieval of objects from within collections of multimedia presentations poses a number of problems but also offers opportunities for enhancing retrieval performance, by utilising information about the relationships between objects. This paper is concerned with the theoretical possibility of using the synchronisation information contained in SMIL-compliant multimedia presentations to retrieve objects which may either lack appropriate metadata or where the metadata is insufficient to enable reliable retrieval. It suggests that the synchronicity of display of objects could be used to infer their content and that this would provide possibilities for enhancement of retrieval performance. It further suggests how this process might be achieved and recommends that an experimental collection of SMIL-compliant presentations needs to be established to enable experimental work to be undertaken.